Process synthesis using block superstructure with automated flowsheet generation and optimization - Li, Jianping; Demirel, Salih Emre; Hasan, M. M. Faruque (AIChE journal, 2018)
An alternative method for chemical process synthesis using a block‐based superstructure representation is proposed. The block‐based superstructure is a collection of blocks arranged in a two‐dimensional grid. The assignment of different equipment on blocks and the determination of their connectivity are performed using a mixed‐integer nonlinear formulation for automated flowsheet generation and optimization‐based process synthesis. Based on the special structure of the block representation, an efficient strategy is proposed to generate and successively refine feasible and optimized process flowsheets. Our approach is demonstrated using two process synthesis case studies adapted from the literature and one new process synthesis problem for methanol production from biogas © 2018 American Institute of Chemical Engineers AIChE J, 64: 3082–3100, 2018